Modeling of the filtration processes in a rectangular area soils using the Darcy - Olijnyk, Andrij; Shtaier, Lidiia; Belei, Oksana; Stasyuk, Rоman; Yasinetska, Iryna (Eastern-European Journal of Enterprise Technologies, 2017)
In the framework of the research described in this paper we implemented the numerical algorithm and the program for the implementation of the algorithm, which makes it possible to calculate pressure field in the examined region and established convergence of the iterative process at optimal selection of the relaxation parameter. The obtained results enable carrying out estimation of the ground water level and propagation patterns under conditions of appropriate environmental characteristics of flow in the presence of varying geometrical configuration of outflow zones through the examined surface. The modelling of filtration processes in a rectangular plot of soil using the Darcy equations might also be used in the problems on estimating water quality, in the tasks on preventing flood waters, floods or mudflows. Such a simulation also makes it possible to explore the phenomena of fluid propagation in soils given the prospects of development of shale gas deposits in the regions of Lviv, Ternopil, Ivano-Frankivsk oblasts (Ukraine). Thus, the applied aspect of the use of the obtained scientific result is the possibility to improve the developed mathematical model of filtration processes through the inclusion of morphological characteristics of river and the river system. This is a prerequisite for obtaining operational data on a change in the level of soil and flood waters at a specified point in time in order to ensure ecological safety of the environment